Italian Community Psychology in the COVID-19 Pandemic: Shared Feelings and Thoughts in the Storytelling of University Students - Di Napoli, Immacolata; Guidi, Elisa; Arcidiacono, Caterina; Esposito, Ciro; Marta, Elena; Novara, Cinzia; Procentese, Fortuna; Guazzini, Andrea; Agueli, Barbara; Gonzáles Leone, Florencia; Meringolo, Patrizia; Marzana, Daniela (Frontiers in Psychology, 2021)
This study investigated how young Italian people experienced the moment of maximum spread of Covid-19 in their country by detecting their emotions, thoughts, events and actions related to interpersonal and community bonds. This approach to the pandemic will highlight social dimensions that characterized contextual interactions in the specific perspective of Community Psychology. The aim was to investigate young people’s experiences because they are the most fragile due to their difficulty in staying home and apart from their peers and, at the same time the most potentially dangerous people due to their urge to group together. The research involved 568 university students, 475 females and 93 males, with an average age of 21.82 years (SD = 4.836). The collected data were analyzed through Grounded Theory Methodology, using the Atlas 8.0 software. From the textual data, representative codes were defined and grouped into twelve categories which reflect the individuals' prosocial attitudes, behaviors and values and were summarized by a visual core category including two meaningful images reported by texts. These categories formed three macro-categories: called ‘Collective Dimensions”, which include Connection, Sharing, Solidarity, Attention to Social Problems, Negative Approach to the World, Social Mourning and Italia-ness; ‘Proactive Orientation’, which includes Trust and Hope; and ‘Collective Values’, which includes Values of Freedom, Respect of social rules and Civic-mindedness. All these macro-categories are indicative of the common sentiment experienced by Italians during the darkest moment of the pandemic. Further practical implications of these results will be discussed considering also the risk of developing distress and improving well-being, as well as promoting preventive behaviors.